PENERAPAN TEKNIK FISIOTERAPI DADA TERHADAP KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS PADA ANAK DENGAN PENYAKIT SISTEM PERNAFASAN - Nova Ari Pangesti; Riski Setyaningrum (MOTORIK Jurnal Ilmu Kesehatan, 2020)
Respiratory disease is a condition where there is a problem in respiratory system. Some of disease include in respiratory disease are pneumonia, asthma, and bronchitis. Child who experience respiratory tract disorders often occur an increase in the production of excessive phlegm in the lungs of phlegm which thicknes and accumulates so that it is difficult to remove, therefore to help speed healing assisted by chest physiotherapy. The aim is to know the effect of chest physiotherapy on ineffective of clearance airway on a child with respiratory disorders. This research use literature review as method to know the effect of chest physiotherapy. The result of research After performing chest physiotherapy, airway clearance of child effectively with the criteria for respiratory frequency within normal limits, being able to remove sputum, no additional breath sounds, and coughing decreased. Chest physiotherapy are significantly effective to overcome ineffective airway clearance.